2017
DOI: 10.1038/srep39902
|View full text |Cite
|
Sign up to set email alerts
|

Katanin p80, NuMA and cytoplasmic dynein cooperate to control microtubule dynamics

Abstract: Human mutations in KATNB1 (p80) cause severe congenital cortical malformations, which encompass the clinical features of both microcephaly and lissencephaly. Although p80 plays critical roles during brain development, the underlying mechanisms remain predominately unknown. Here, we demonstrate that p80 regulates microtubule (MT) remodeling in combination with NuMA (nuclear mitotic apparatus protein) and cytoplasmic dynein. We show that p80 shuttles between the nucleus and spindle pole in synchrony with the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Although we have not observed any direct link between katanin and SPEF2, the phenotypic similarities suggest that they might function in the same pathway. Just like SPEF2, KATNB1 has been shown to interact with cytoplasmic dynein (Jin et al, 2017). However, while we showed that SPEF2 is likely to function downstream of dynein, KATNB1 has been shown to inhibit dynein motility, suggesting that it functions as an upstream regulator of dynein.…”
Section: Discussionmentioning
confidence: 57%
“…Although we have not observed any direct link between katanin and SPEF2, the phenotypic similarities suggest that they might function in the same pathway. Just like SPEF2, KATNB1 has been shown to interact with cytoplasmic dynein (Jin et al, 2017). However, while we showed that SPEF2 is likely to function downstream of dynein, KATNB1 has been shown to inhibit dynein motility, suggesting that it functions as an upstream regulator of dynein.…”
Section: Discussionmentioning
confidence: 57%
“…Notably, patient mutations in KATNB1 were unable to elicit aster formation. In the same study, it was shown that p80 and/or NuMA down-regulation induces neural progenitors to exit the proliferation phase and prematurely commit to neuronal differentiation, in addition to delaying neuronal migration in the mouse embryonic brain [278].…”
Section: Atypical Rare Cases Consanguineous Families and Contributiomentioning
confidence: 91%
“…Hu and col. [277] showed that patient-derived cells had decreased levels of both p80 and p60 proteins, as well as mitotic and signaling abnormalities. More recently, it was demonstrated that p80 regulates MT remodeling in combination with its interacting partner NuMA (nuclear mitotic apparatus protein) and cytoplasmic dynein, and that p80 is essential for aster formation and maintenance in vitro [278]. Notably, patient mutations in KATNB1 were unable to elicit aster formation.…”
Section: Atypical Rare Cases Consanguineous Families and Contributiomentioning
confidence: 99%
See 2 more Smart Citations